Eco-tourism, FinTech, and resource governance as strategic drivers of CO2 mitigation in emerging economies: insights from quantile regression analysis - Jiang, Lijuan; Hassan, Afnan (Frontiers in Environmental Science, 2025)
This study explores the role of tourism, financial technologies (FinTech), and resource governance as strategic drivers of CO2 mitigation in emerging economies, specifically in E7 nations. Using panel data spanning the period 2000 to 2022, the research investigates how tourism, FinTech—defined as digital innovations in financial services including green finance—and resource governance, measured through natural resource rents, contribute to reducing carbon emissions. The study employs Method of Moments Quantile Regression (MMQR) to examine the heterogeneous effects of these variables across different levels of CO2 emissions and applies Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) for robustness testing to ensure the reliability of the findings. The results reveal that while economic growth and urbanization tend to exacerbate emissions, eco-tourism, FinTech, and resource governance exhibit varying impacts across emission quantiles. Notably, eco-tourism demonstrates strong potential in mitigating CO2 emissions, especially in regions facing higher environmental stress. This study emphasizes the importance of targeted policies that promote sustainable tourism practices, harness FinTech for green innovation, and reinforce resource governance. By offering actionable policy insights, it provides a roadmap for E7 nations to integrate these strategic levers into their climate action agendas, thereby advancing both environmental and economic sustainability.